How to balance teacher’s guidance and learner autonomy in the classroom - Babaxanova, Dildora Ikromjon qizi (The Lingua Spectrum, 2026)
This article addresses the challenge of balancing teacher guidance and learner autonomy in modern foreign language education. While traditional approaches often prioritize structured instruction and teacher control, contemporary perspectives emphasize learner independence and active engagement in the learning process. The study explores how these elements can be effectively integrated to create a supportive and productive learning environment. Drawing on theories of second language acquisition, sociocultural theory, and learner-centered pedagogy, the article examines key concepts such as scaffolding, metacognitive strategies, and interactive learning practices. It highlights the evolving role of teachers as facilitators who provide guidance while encouraging learners to take responsibility for their own progress. Practical recommendations include the use of task-based learning, collaborative activities, and reflective practices to support balanced instruction. The findings suggest that combining guidance with autonomy enhances motivation, promotes deeper learning, and strengthens communicative competence, ultimately preparing learners for independent and effective language use in diverse real-life contexts and future academic or professional settings.